Mindfulness-Based Intervention for People With Dementia and Their Partners: Results of a Mixed-Methods Study - Berk, Lotte; Warmenhoven, Franca; Stiekema, Annemarie P. M.; van Oorsouw, Kim; van Os, Jim; de Vugt, Marjolein; van Boxtel, Martin (Frontiers in Aging Neuroscience, 2019)
Objectives. Studies have shown preliminary support for mindfulness-based interventions benefitting people with dementia and their caregivers. However, most studies focus on these two groups separately. This study examined whether it would be possible and beneficial for people with dementia and their caregiver to jointly undergo an adjusted Mindfulness-Based Stress Reduction (MBSR) training, named TANDEM. Method. The 8-week MBSR training was adjusted based on a literature review and interviews with experts (clinicians and mindfulness trainers). Seven couples (a person with early-stage dementia and their caregiver) participated together in the 8-week TANDEM program. Semi-structured qualitative interviews were conducted after completion. Questionnaires (administered before and after the intervention) assessed the primary outcomes of quality of life and psychological distress (stress, anxiety and depressive symptoms). Secondary outcomes were mindfulness, self-compassion, positive mental health, worrying, and perceived burden (for caregivers). Results. All participants completed the program and reported beneficial effects (relaxation, awareness, acceptance, and resilience). Most managed to integrate exercises into their daily lives and planned to continue their practice. Participating in a group was considered valuable and supportive. Furthermore, it was appreciated that participants could follow the training together (as a couple). The quantitative results showed a small effect on increased quality of life for caregivers. No substantial decrease in psychological distress was apparent. Caregivers displayed a large increase in mindfulness. Conclusions. The results of this mixed-methods study suggest that an adjusted mindfulness program is feasible and well-received among couples of persons with early-stage dementia and their caregiver, warranting further research in this area.